An exploratory study of close supplier-manufacturer relationships - Goffin, Keith; Lemke, Fred; Szwejczewski, Marek (Elsevier Science B.V., Amsterdam., 2006)
Close relationships with selected suppliers can enable manufacturers to reduce costs, improve quality and enhance new product development. Although the advantages of close co-operation are widely acknowledged in the literature, the specific attributes of such relationships are not well understood. To address this gap, 39 managers responsible for purchasing were interviewed using a technique from psychology, which is particularly effective at uncovering the characteristics of relationships. This approach is innovative in the context of supplier management research and gave insights into how manufacturers expect more from their suppliers than just reliable deliveries of high-quality, well- priced parts and components. The results of the empirical research enhance our knowledge of the attributes of manufacturer–supplier relationships and also indicate how manufacturers can establish close relationships with selected suppliers. Overall, the study has established the viability of a new approach for understanding the complex topic of manufacturer–supplier partnersh
Keywords: Purchasing; Supply management; Relationships; Partnership; Supplier base